Identifi kasi Senyawa β-Sitosterol dari Ekstrak n-heksan Daun Mimba (Azadirachta indica A. Juss) dan Uji Penghambatan Enzim α-Glukosidase - Ivan Santoso; Partomuan Simanjuntak; Rahmaniar Rahmaniar (Fakultas Farmasi Universitas Pancasila, 2017)
Mimba, Azadirachta indica is one of the family Meliaceae plants, which be used to lower blood sugar and contain terpenoids, fl avonoids, alkaloids, saponins, tannins, fatty acids, steroids and triterpenoids. The aim of this research is to isolate and identify one of chemical structure and to know the inhibition α-glucosidase enzyme from extract of leaves Mimba, Azadirachta indica. Extraction is done by maceration using n-hexane, ethyl acetate, methanol, water and then treatment for antidiabetic activity using the inhibition of the enzyme α-glucosidase. Purifi cation of n-hexane extract (the higher activity) is subjected by column chromatography (SiO2; (i).n-hexane-ethyl acetate = 10 : 1 1 : 1, ethyl acetate, (ii). n-hexane-ethyl acetate = 5 : 1) gave one pure compound as white powder. Identifi cation by interpretation of spectra [UV, IR and NMR (1H, 13C-NMR and DEPT)] the isolate compound is β-sitosterol has inhibion α-glucosidation enzyme as (IC50 208,1 μg/mL).